2020
DOI: 10.3390/cells9051198
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function for KLF4 in Modulating the De-Differentiation of EpCAM−/CD133− nonStem Cells into EpCAM+/CD133+ Liver Cancer Stem Cells in HCC Cell Line HuH7

Abstract: The complex and heterogeneous nature of hepatocellular carcinoma (HCC) hampers the identification of effective therapeutic strategies. Cancer stem cells (CSCs) represent a fraction of cells within tumors with the ability to self-renew and differentiate, and thus significantly contribute to the formation and maintenance of heterogeneous tumor mass. Increasing evidence indicates high plasticity in tumor cells, suggesting that non-CSCs could acquire stem cell properties through de-differentiation or reprogramming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 83 publications
1
32
0
Order By: Relevance
“…Second, the existence of intertumor, intratumor, and CSC heterogeneity is a daunting challenge in the development of immunotherapy targeting HCC CSCs 23 , 178 . Additionally, several studies have demonstrated that the HCC CSCs are plastic and can be converted from tumor cells without a stem phenotype, which can be induced by virus infection, crosstalk between CSCs and tumor cells, hypoxia stimulation, and conventional therapies 76 , 77 , 106 , 179 , 180 . This plasticity and instability of the CSC phenotype in HCC is a major obstacle for effective immunotherapy targeting CSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the existence of intertumor, intratumor, and CSC heterogeneity is a daunting challenge in the development of immunotherapy targeting HCC CSCs 23 , 178 . Additionally, several studies have demonstrated that the HCC CSCs are plastic and can be converted from tumor cells without a stem phenotype, which can be induced by virus infection, crosstalk between CSCs and tumor cells, hypoxia stimulation, and conventional therapies 76 , 77 , 106 , 179 , 180 . This plasticity and instability of the CSC phenotype in HCC is a major obstacle for effective immunotherapy targeting CSCs.…”
Section: Resultsmentioning
confidence: 99%
“…High expression of CD133 was positively associated with poor overall survival in HCC patients. CD133 may facilitate CSC characteristics via stabilizing EGFR-Akt or regulating neurotensin/interleukin (IL)-8/CXCL1 pathway 50 , 51 . The results from our 3D formation and CD133, E2F1/3 expression assays indicated that Tiliroside has displayed its anti-stemness ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence also indicated that Klf4 could promote the expression of cancer stem cell-related markers and mesenchymal markers in colon cancer cells [67]. Similarly, in hepatocellular carcinoma cells, Klf4 can convert regular cancer cells into a cancer stem celllike phenotype by positively regulating the expression of EpCAM and E-CAD [68]. Researchers also confirmed that Klf4 acted as a potent oncogene in breast cancer development via facilitating cell invasion, migration, and the maintenance of stem cell features [69].…”
Section: The Function Of Pluripotent Genes In Carcinogenesismentioning
confidence: 95%